The Network Structure of the Forestry Research as a Scientific Field in Turkey between 1999 and 2019 - Dervis, Hamid; Ayan, Sezgin (Hrvatski Sumarski Institut (Croatian Forest Research), 2021)
This study aims to analyse and map the network structure of the scholarly communications in the realm of forestry research between 1999 and 2019 in Turkey using bibliometric analysis and social network analysis methods of the articles published within Clarivate Analytics’ Web of Science (WoS). A total of 8689 records, including their bibliographic data, were extracted from WoS. The analysis of each sub-period shows that the number of international collaboration of Turkish authors has increased globally from 23 countries in the first sub-period to 113 countries in the last sub-period within forestry publications. Also, the annual percentage rate of publications has increased from 58 articles in 1999 to 1016 in 2019 in the realm of forestry alongside with their received average citations in each sub-period. Multi-author articles precede single-author articles in the field of forestry in each sub-period. This research is the first analysis of forest research production using bibliometric and network analysis in Turkey. According to the results biomass, remote sensing and climate change were current trends on forest research in Turkey. Incidentally, the research findings can be used by policymakers regarding future investments in forestry research development.
Keywords: forestry publication; bibliometric; social network analysis; Forestry; forestry science mapping; SD1-669.5; 15. Life on land